(untitled) (Innovaciones Educativas, 2024)
The aim of this article is to analyse the self-perception of media literacy among Chilean journalism teachers, focusing on the ability to produce and distribute content in an ecosystem of digital platforms (production and distribution processes dimension of media literacy). The methodology follows a quantitative approach, based on an online questionnaire applied to 213 journalism teachers belonging to 26 Chilean universities between May and October 2013. The results reveal some paradoxes: although 41% of the sample consider themselves to have a high level of ability to produce and disseminate content on digital platforms, a significant percentage (35%) are at a low level. Differences are also observed in some of the independent variables considered: women perceive themselves at a lower level than their male colleagues; the higher the age, the lower the production of content on platforms or social networks; the territorial difference indicates that teachers in non-metropolitan regions perceive themselves as having a higher level of competence, although they do not disseminate content frequently; and the self-perception of competence is particularly low on platforms such as TikTok and YouTube. These findings pose important challenges in the dimensions related to the processes of production and dissemination of content by journalism teachers, especially when we consider that the media and information consumption of their students is centred precisely in these digital spaces.